Pemaknaan Pesan Self Love Penggemar BTS dalam Lagu "Answer: Love Myself" - Dhea Aurel; Lusia Savitri Setyo Utami (Kiwari, 2026)
Music functions not only as a form of entertainment but also as a symbolic medium through which emotional messages are communicated and individuals’ self-understanding is shaped. One prominent theme in contemporary popular music is self-love, as exemplified in Answer: Love Myself by BTS. This study aims to explore how BTS fans, known as ARMY, interpret and internalize the self-love message conveyed in the song’s lyrics. Employing a qualitative phenomenological approach, the study examines the subjective experiences of six active BTS fans. Data were collected through in-depth interviews and complemented by expert insights from a psychologist to enrich the interpretive analysis. The findings reveal that the interpretation of the song’s self-love message is shaped by participants’ cognitive schemas, prior emotional experiences, and the social support they receive from the ARMY community. The lyrics are perceived as affirming, emotionally warm, non-patronizing, and accepting, thereby reducing listeners’ psychological defensiveness and enabling deeper emotional engagement. The process of internalization occurs through self-reflection, heightened self-awareness, and the integration of the song’s meaning into individuals’ self-concept. This study underscores the significant role of music as an effective symbolic and emotional medium in fostering self-love and emotional resilience among adolescents and young adults. It further contributes to broader discussions on the communicative and therapeutic potential of popular music in supporting psychological well-being and identity development. Musik berperan sebagai medium simbolik yang mampu menyampaikan pesan emosional dan membentuk pemaknaan individu terhadap diri sendiri. Salah satu pesan yang menonjol dalam musik populer adalah self-love, seperti yang terdapat dalam lagu “Answer: Love Myself” oleh BTS. Penelitian ini bertujuan untuk memahami bagaimana penggemar BTS, yang dikenal sebagai ARMY, memaknai pesan self-love yang disampaikan dalam lirik lagu tersebut. Penelitian ini menggunakan pendekatan kualitatif fenomenologi dengan melibatkan enam informan yang merupakan penggemar BTS aktif. Data dikumpulkan melalui wawancara mendalam dan diperkuat dengan analisis narasumber ahli dari seorang psikolog. Hasil penelitian menunjukkan bahwa pemaknaan pesan self-love dipengaruhi oleh skema kognitif, pengalaman emosional masa lalu, serta dukungan sosial dari komunitas ARMY. Lirik lagu dipersepsikan sebagai pesan yang positif, hangat, tidak menggurui, dan menerima, sehingga membantu menurunkan mekanisme defensif pendengarnya. Pesan tersebut kemudian diinternalisasi melalui refleksi diri, peningkatan kesadaran diri, serta integrasi makna ke dalam konsep diri individu. Studi ini menegaskan peran musik sebagai medium efektif dalam memfasilitasi pengembangan self-love pada remaja dan dewasa muda.